Comparison study of thermal insulation characteristics from oil palm fibre - Hassan, S. (EDP Sciences, 2014)
In this study, investigation was conducted to study the use of solid biomass from palm oil mill as insulation material. The experimental study concentrates on using oil palm fiber to determine the unidirectional thermal conductivity, k. The experiment was conducted at different temperature ranges and packing density. The values of k obtained were found to be 0.2 W/m.K to 0.069 W/m.K for a packing density between 66 kg/m3 to 110 kg/m 3, and at a temperature between 40°C to 70°C. Comparisons were made with others common insulating materials, and it was found that the experimental k values for oil palm waste insulation was lower by between 4 to 56 times for rockwool and between 7 to 57 times for glass fiber at low temperatures. The value k of oil palm fiber however showed an increase at higher temperatures and was lower at lower packing densities. Although not being able to match the k values of common insulators at higher temperatures, other factors such as cost and environmental benefits of using waste material should be taken into consideration and hence encouraging its use as at least a supplement to existing insulation materials. © 2014 Owned by the authors, published by EDP Sciences.